Development of a Dialectical Behavior Therapy Intervention Package for Patients with Obesity - Saeidiasl , Sahar; Moraveji, Mahtab; Moallem , Masoumeh; Hobbi , Mohamad Bagher; Manzari Tavakoli , Vahid (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to develop a dialectical behavior therapy (DBT) intervention package for patients with obesity. This study was qualitative in nature and employed a meta-synthesis strategy with a synthesis research approach to extract the components of the therapeutic package from valid sources. To determine the sample, two sampling frameworks were considered: (1) studies accessible through computerized databases, including the Noor Specialized Journals Database, the Iranian Journals Database, the Academic Center for Education, Culture and Research (ACECR) Scientific Database, and Google Scholar; and (2) student theses available in the Iranian Research Institute for Information Science and Technology (IRANDOC). Subsequently, findings related to the selected documents within the relevant research domain were analyzed, coded, and categorized with the aim of developing a DBT intervention package for patients with obesity as a novel product, and the main themes of the therapeutic package were extracted. After validation using the Content Validity Index (CVI) and the Content Validity Ratio (CVR) by a panel of 15 experts, the intervention package was finalized. Based on the obtained data and prior studies, DBT was coded and categorized into eight therapeutic themes: conceptualization, distress tolerance and flexibility, states of mind, emotion regulation, nutrition and body-related considerations, chain analysis of events influencing overeating, management of maladaptive behaviors and cognitive patterns, and mindfulness. These findings can be utilized in psychological intervention programs for patients with obesity.